Encyclopedia of mammals: A comprehensive illustrated guide by international experts (San Diego, California, 1998)
Encyclopedia of Mammals features new conservation information of each order, highlighting the three levels of threat - critically endangered, endangered, and vulnerable. Statistics regarding the number of families, genera, and species within each of the orders and the number of endangered species have been amended to reflect the most recent data. The book is complemented by over 200 superb photographs and over 100 original paintings, diagrams, and maps to give an up-to-date overview of our knowledge of the once-secret lives of mammals
Keywords: mammals